Optimalisasi Potensi Desa Melalui Pelatihan dan Pendampingan UMKM Berbasis Digital - Daniel Aditia Lao; Widya Sari Manurung; Mia Rahayu; Muh Faisal; Haris Fatkhurohman; Ivan Valdis; Margaretha Irene Nauw; Edoardus Bavo Futwembun; Arlen Faiz Akbar; Danang Sunyoto (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Villages have great economic potential, especially through the role of Micro, Small, and Medium Enterprises (UMKM). Which are the backbone of the community's economic activities. However, many UMKM in villages still face obstacles in managing their businesses, marketing, and utilizing digital technology. Based on these problems, the Real Work Lecture (KKN) program is focused on efforts to Optimize Village Potential Through Digital-Based UMKM Training and Mentoring. The purpose of this activity is to increase the capacity of village UMKM actors so that they are able to manage their businesses effectively and utilize digital technology in product marketing. The methodology used in this program includes initial observation, identification of UMKM needs, implementation of digital marketing training, use of social media and marketplaces, and direct ongoing mentoring. This activity is carried out in a participatory manner by involving MSME actors, village officials, and KKN students. The expected results of this activity are increased knowledge and digital skills of UMKM actors, the formation of stronger local product branding, and increased competitiveness of village UMKM in a wider market. This program is expected to be the first step towards technology-based village economic independence.